We are given the following 2x2 matrix
![A=\begin{bmatrix}{-3} & {-2} \\ {4} & {8}\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/e1jsnzm5nidb2wlt8l84yphi7j0bdp4rqr.png)
We are asked to find the inverse of matrix A.
Recall that the inverse of a 2x2 matrix is given by
![A^(-1)=(1)/(ad-bc)*\begin{bmatrix}{d} & {-b} \\ {-c} & {a}\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/lwao24bduu94er0mdtqbor5f86umjbfah7.png)
Where
a = -3
b = -2
c = 4
d = 8
Let us substitute these values into the above equation
![A^(-1)=(1)/((-3)(8)-(-2)(4))*\begin{bmatrix}{8} & {-(-2)} \\ {-(4)} & {-3}\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/pyuc8c9pgijoq68zk8u9a5mw1ram135gux.png)
Now simplify
![\begin{gathered} A^(-1)=(1)/(-24+8)*\begin{bmatrix}{8} & {2} \\ {-4} & {-3}\end{bmatrix} \\ A^(-1)=(1)/(-16)*\begin{bmatrix}{8} & {2} \\ {-4} & {-3}\end{bmatrix} \\ A^(-1)=\begin{bmatrix}{(8)/(-16)} & {(2)/(-16)} \\ {(-4)/(-16)} & {(-3)/(-16)}\end{bmatrix} \\ A^(-1)=\begin{bmatrix}{-(1)/(2)} & {-(1)/(8)} \\ {(1)/(4)} & {(3)/(16)}\end{bmatrix} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w5maqpb9iyqjyssn1qe2ofq4pemvkrumvf.png)
Therefore, the inverse of the matrix A is
![A^(-1)=\begin{bmatrix}{-(1)/(2)} & {-(1)/(8)} \\ {(1)/(4)} & {(3)/(16)}\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/5l4bcp38ydwi11wy0850o4gs4lu5d345eg.png)